2002
DOI: 10.1002/1521-4141(200212)32:12<3785::aid-immu3785>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Lack of deleterious somatic mutations in the CD95 gene of plasmablasts from systemic lupus erythematosus patients and autoantibody-producing cell lines

Abstract: The interaction of CD95 with its ligand CD95L is important for negative selection of B cells during the germinal center (GC) reaction. Recently, mutations confering restistance to CD95‐induced apoptosis have been described for human GC B cells. Hence, as has been demonstrated for CD95‐deficient mice, also GC‐derived autoreactive B cells carrying somatic CD95 gene mutations may potentionally survice negative selection and participate in the development of autoimmune diseases. Here, single plasmablasts (PB) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Based on a Taq DNA polymerase error rate of 10 Ϫ5 /bp and cycle, 14,15 we expected 1 error/2857 bp and 1 error/3333 bp for PAX5 (35 cycles) and RhoH/TTF (30 cycles), respectively. Considering the number of base pairs of the individual sequences and the number of sequences analyzed (18,20, and 20 for PAX5, patients 2 and 10, and for RhoH/TTF, patient 10, respectively), one would have expected the introduction of 6, 6, and 5 mutations because of Taq DNA polymerase errors for PAX5, patients 2 and 10, and for RhoH/TTF, patient 10, respectively. With 18, 27, and 7 point mutations in patient 2 and patient 10 for the PAX5 gene and in patient 10 for the RhoH/TTF gene (Table 2), respectively, the number of point mutations is clearly above this threshold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a Taq DNA polymerase error rate of 10 Ϫ5 /bp and cycle, 14,15 we expected 1 error/2857 bp and 1 error/3333 bp for PAX5 (35 cycles) and RhoH/TTF (30 cycles), respectively. Considering the number of base pairs of the individual sequences and the number of sequences analyzed (18,20, and 20 for PAX5, patients 2 and 10, and for RhoH/TTF, patient 10, respectively), one would have expected the introduction of 6, 6, and 5 mutations because of Taq DNA polymerase errors for PAX5, patients 2 and 10, and for RhoH/TTF, patient 10, respectively. With 18, 27, and 7 point mutations in patient 2 and patient 10 for the PAX5 gene and in patient 10 for the RhoH/TTF gene (Table 2), respectively, the number of point mutations is clearly above this threshold.…”
Section: Resultsmentioning
confidence: 99%
“…19 Furthermore, the observation of autoreactive diseases suggested a link between CD95 mutation, lymphomagenesis, and autoimmunity, although this is still controversially discussed because CD95 gene mutations appeared to play little, if any, role in the generation of the pool of plasmablasts in patients with systemic lupus erythematosus. 13,20 However, although CD95 mutations alone are unlikely to commit a GC B cell to malignant transformation, they may represent an early event in lymphomagenesis by favoring the persistence of mutant GC B cells, which may acquire additional transforming modifications, ultimately resulting in malignant lymphoma formation. In this context it is interesting that PCNSLs preferentially rearranged the V4-34 gene segment, which has been implicated in autoimmune disorders, including cold agglutinin disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent immunohistochemical studies have identified directly infected memory and germinal center cells which express EBNA2 and appear to have undergone EBV-driven clonal expansion (27,28) in the tonsils of AIM patients. The infection of all B-cell subsets in the tonsils of healthy carriers has also been seen (4); however, in this case, each subset uses a discrete transcription program and EBNA2 was not detected in the memory or germinal center cells.…”
Section: Discussionmentioning
confidence: 99%
“…These ideas in turn imply that the EBV-driven lymphomas associated with immunosuppression occur because of inappropriate infection of B cells, i.e., in a form or location where they cannot differentiate out of the proliferative state, an event we refer to as bystander infection. Such events are seen in acute AIM patients' tonsils, which contain infected memory and germinal center cells clonally expanding under the influence of EBNA2 (30,31). These types of cells are not present in healthy carriers (10,11) and, therefore, do not relate to the biology of persistence.…”
Section: ) the Exception Is That When The Cells Divide They Expresmentioning
confidence: 99%